Security architecture to support multiple security policies based on access control space - LI Li-ping1; QING Si-han1; HE Ye-ping1; SHEN Qing-ni1 (Tongxin xuebao)
In order to solve the problems of policy reusability and policy co-existence in LSM,a new security architecture ELSM is proposed.It introduced Model Combiner as main module to implement module stack management and module decision management.Module decision is based on access control space as policy specification for general support.The design of ELSM and the analysis of its implementation in Ansheng OS prove its effectiveness.